Knowledgebase of smokeless tobacco products and their chemicals - Harpreet Singh; Jasmine Kaur; Arun Sharma; Amit Kumar; Suchitra Kumari; Deeksha Bhartiya; Dhirendra Sinha; Ravi Mehrotra (Tobacco Induced Diseases, 2018)
Background Smokeless tobacco (SLT) products vary in appearance and in their composition of tobacco and non-tobacco chemical constituents thus differing in the mode of consumption. They may be consumed orally (chewed, sucked, dipped, held in the mouth, etc.) or nasally resulting in absorption of nicotine and other chemicals across mucus membranes. It is estimated that tobacco contains roughly 4,000 chemical constituents which undergo various chemical changes till the final SLT product is formed. Some of these are identified as potent carcinogens and are believed to play a crucial role in causing the negative health effects associated with SLT use.